Rational pharmacotherapy of major vaginal diseases - A G Kedrova (IP Berlin A.V., 2014)
This paper outlines the issues of rational pharmacotherapy for women with various vulvovaginal etiology. Taking into consideration the pathogenesis of major diseases of the vagina, the concept of therapy based on combined drugs. Implementation of safe dosage forms of metronidazole, mikоnazole and lidocaine (Neo-Penotran® Forte L) allowed to quickly relieve symptoms of acute discomfort sensations in patients with symptomatic vulvоvaginitov, relieving pain, usually manifested in the form of burning, itching, edema, hyperemia of the vestibule and perineal tissues, allowed to achieve maximal compliance during treatment and achieve not only clinically but also pathogenic effect.The combination of metronidazole and mikоnazole showed a dose-dependance efficiency that depends on the type and form of the disease pathogens vagina, as this combination of drugs had a positive impact on the recurrent form of the disease.